Experimental study of adjustable throttle influence on the linear parameters of the hydraulic system - Чуйко, Всеволод Петрович (Eastern-European Journal of Enterprise Technologies, 2014)
Analysis of the approaches to solving the problem of operational control of the hydraulic system parameters was performed in the paper. The paper describes a method of providing uniform motion of the output link of the hydraulic motor by setting the adjustable throttle on the discharge manifold of the hydraulic system. Throttle generates pressure pulsations in the discharge chamber, which compensate sharp pressure increase in the pressure chamber of the hydraulic motor. Throttle parameters, providing a constant speed of the output link are calculated. Based on the calculation results, the design of an adjustable throttle with a rotating spool is developed. The description and operation principle of the designed adjustable throttle, the scheme of its inclusion in the hydraulic network are given. The developed test bench of the throttle and its operation principle are described. The paper presents the results of functional tests of the designed adjustable throttle. The results of theoretical and empirical research, based on which it was concluded on a fundamental confirmation of the proposed method of pulsation dampening in the hydraulic system are compared.